COMPARISON OF AMELIORATIVE EFFECTS OF ESSENTIAL OIL AND ETHANOLIC EXTRACT OF NIGELLA SATIVA SEED IN ACETAMINOPHEN INDUCED LIVER DAMAGE. - DR.DEVENDRA SINGH KUSHWAH, (International Journal of Pharma and Bio Sciences, 2014)
Adverse drug effects are a major limitation of modern medical practices. Herbs play an important role in the management of various liver disorders. This study was designed to investigate the hepatoprotective activity of ethanolic extract and essential oil of Nigella sativa (kalonji) in paracetamol induced acute liver toxicity in rats. For this purpose fasted male Wistar rats, 225-250 g in weight, were orally treated with Nigella sativa extract (NSE) in graded doses, silymarin or vehicle for 7 days followed by paracetamol (PCM) 3 g/kg on 8th day. 24 hrs after PCM administration rats were sacrificed and histopathology of liver sample was done. Blood was withdrawn before and after the treatment for estimation of circulatory liver markers using semiautoanalyzer. PCM caused a significant increase in serum alkaline phosphatase, glutamic pyruvic transaminase and glutamic oxaloacetic transaminase levels, which were significantly ameliorated in groups receiving NSE or silymarin in a dose dependant manner. Liver histopathology showed marked reduction in sinusoidal dilatation, midzonal necrosis, portal triditis and occasional apoptosis in NSE treated group as compared to group receiving only PCM. The present results indicate that NSE possesses hepatoprotective action against PCM induced acute hepatoxicity. Further research is needed to advocate its use in prevention of drug induced hepatotoxicity.